THE IMPORTANCE OF CREATIVE WORKS DURING THE TIME OF AMIR TEMUR (IN THE CASE OF THE SHAHRISABZ STATE MUSEUM RESERVE) (Journal of Universal Science Research, 2023)
In this article, the author notes that Amir Timur's enormous contribution to thestate system, the development of science, education and culture.  During the reign of the Temurids, there was a flourishing not only of art crafts, but also of books, calligraphy, art of miniature, several schools of miniaturists existed at once. There is evidence that there was a rich library, a collection of books from all the conquered countries.